PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA KARYAWAN ( STUDI KASUS PADA PUSKESMAS SEGIRI ) - Tandiarrang, Sarlotha (EKONOMIA, 2014)
Formulation of the problem as posed in this study are: "Is there a significant effect of leadership (X1) and organizational culture (X2) on the  effectiveness of employees ( Y ), if  there is a significant effect of  leadership ( X1 ) of the Employee Effectiveness (Y) and whether there is a significant effect of organizational culture (X2 ) the effectiveness of employees (Y) ".The purpose of this study was to determine whether there is leadership and  organizational  culture influences the  effectiveness  of employees. And in particular to determine how much influence the leadership and organizational culture on employee effectiveness.This research was  conducted at  the  PHC Segiri in  Samarinda. Data sources include primary data and secondary data, using quantitative methods, data collection techniques using questionnaires, population 33 employees and instrument measurement techniques using a Likert scale.The hypothesis in this study suggests that there is a significant relationship between leadership (X1) and organizational culture (X2) on the effectiveness of employees (Y), there was a significant effect of leadership (X1) on the effectiveness of employees, there is a significant effect of organizational culture (X2 ) the effectiveness of employees (Y).The results of this study suggests that there is a significant influence on the effectiveness of employee leadership by 0004, then there is a significant influence of organizational culture on the effectiveness of employees is 0,000 and there is a significant effect of leadership and organizational culture together - equal to the effectiveness of employees for 0000. Value of the correlation between leadership and organizational culture on work effectiveness by 0674 the value of the coefficient of determination equal to 0.454. The influence showed that the higher leadership and organizational culture, the lower the effectiveness of employees. Keywords: Leadership, organizational culture and effectiveness of employees